The legal framework for managing the invasion of Ga-Riba Wetlands by poplar plant, Ga-Riba Village, South Africa - Lioma, Tshifhiwa Enocentia (My University, 2010)
According to the Ramsar Convention of 1971, Wetlands are areas of marshes, firm, peatlands or waterlogged. They are either natural or artificial. They have water that is static or flowing, fresh, brackish or salty and include areas of marine water with the depth, which at low tides does not exceed six meters. Wetlands are regarded as important ecological components of the natural environment because of their richness and ability to support life. Wetlands essentially catch, clean and preserve any water. They are able to reduce the severity of drought and floods by regulating a stream flow. They also control erosion and provide habitat for many different plant and animal species. Wetlands also serve as valuable source of water, fish and grazing for livestock. They are important nesting grounds for birds. Wetland resources are also known to be of socio-economic importance because they provide materials for furniture and craft’s work Ga-Riba wetlands are very important for the community of Ga –Riba because they provide them with food such as fish and birds. Some of the community members make baskets, hats and mats using wetlands grass. They also make pottery using clay from the wetlands. During winter the wetlands are used as areas where traditional initiation for Ga-Riba girls is perfomed. Some people own fields within the wetlands on which they cultivate vegetables, maize and other crops. They also use wetland as grazing areas for their domestic animals such as cattle and goats. The Ga-Riba wetlands are being invaded by one of the alien plant called Populus alba L (Poplar). This type of alien plant, like other alien plants disturbs the ecological stability of the wetlands. Findings of the tests conducted on soil and water indicated that Poplars are changing the nature of the soil and the water of the wetlands. Vegetation survey showed that, wetlands had less vegetation than they were supposed to. With regard to legal instruments to control the invasion of wetlands by alien plants, findings showed that there are insuffient legal instruments which can be utilized.
Thesis (M. Phil. (Environmental Law and Management) -- University of Limpopo, 2010
Keywords: Wetlands invasion; Wetlands -- Law and legislation -- South Africa; Wetland management; Wetland conservation